Whaleboats towing bowhead whale, west coast of Hudson Bay, Canada - Comer, George (Creator); Lockwood, F.C. (Creator) (Ownership Statement: Mystic Seaport, 1897)
View of two whaleboats under sail towing a harpooned bowhead whale, west coast of Hudson Bay, Canada. Inuit crew members are among those on board the boats. Infrastructure Livelihood Title supplied by cataloger. Taken by Captain George Comer (1858-1937), a sealer and whaling captain from East Haddam. He went to sea while still in his teens and was later master of vessels from both New London and New Bedford. Comer participated in voyages involved in polar expeditions and was noted for his studies of Arctic peoples and their environment. Slide prepared by F.C. Lockwood of Brooklyn, New York, from an original photograph by Captain George Comer. Slide was used by Comer to illustrate lectures about his Arctic and seafaring experiences.